Analisis Posisi Utang Luar Negeri Indonesia Sejak Orde Lama Hingga Era Reformasi - M, Mahindah; Rosi, Farur; Yasin, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Indonesian economic history after independence in 1945 to the post-New Order transitional government. Initially, the Indonesian economy experienced difficulties with fluctuating growth, a balance of payments deficit, and a State Revenue and Expenditure Budget (APBN) deficit that continued to grow. The New Order government, which began in 1966, tried to overcome these problems by focusing on economic and social development. Even though it succeeded in achieving high economic growth, the New Order's economic policies left behind several problems such as dependence on foreign capital. A transitional government emerged in 1998 after an economic and political crisis that began with riots in Jakarta. This government was initially expected to be an era of reform, but was later deemed not to provide significant changes. The proposed problem formulation includes the definition of foreign debt, the amount of debt from the Soeharto to Jokowi era, the relationship between the debt position and economic growth, the impact of the global financial crisis on the debt position Indonesia, and how the government pays foreign debt. The research objectives involve understanding the concept of foreign debt, comparing the amount of debt from presidents Soeharto to Jokowi, analyzing the relationship between debt position and economic growth, evaluating the impact of the global financial crisis on Indonesia's debt, as well as understanding debt repayment methods by the government.